Formation of a Special Work Unit for the Optimization of Regional Asset Utilization in the Provincial Government of DKI Jakarta (Case Study: Jakarta Asset Management Center) - Wellyani Wellyani; Achmad Lutfi (Jurusan Ilmu Administrasi Publik, Universitas Lampung, 2024)
This research was conducted to analyze the establishment of specialized unit aimed at optimizing the utilization of regional assets to increase regional original revenue in the Provincial Government of DKI Jakarta. In order to provide Professional asset management services, DKI Jakarta Province restructured the Organization dan Work Procedures of the Regional Asset Management Agency to perform to supporting function for Government affairs in the financial sector, under the name Unit Pengelola Jakarta Management Center (UP JAMC). UP JAMC was established by the Governor of DKI Jakarta Regulation Number 57 of 2022 concerning the organization and Work Procedures of the Badan Pengelolaan Aset Daerah. this research uses a descriptive qualitative method by collecting data from interviews with key informants, the official website of the DKI Jakarta Provincial Government, and the Regional Government Financial Report of DKI Jakarta Province. The result of this study conclude that with the establishment of UP JAMC, the utilization of regional assets has increased and contributed to the enhancement of regional original revenue.